Thermodynamic comparison of TF33 turbofan engine fueled by hydrogen in benchmark with kerosene. (15th December 2021) - Balli, Ozgur; Ozbek, Emre; Ekici, Selcuk; Midilli, Adnan; Hikmet Karakoc, T.
Highlights: Development of thermodynamic analysis of TF33 turbofan engine fueled by hydrogen in benchmark with kerosene. Comparative analysis of performance, environmental, and sustainability assessments for hydrogen-TF33. Presentation of the superiority and inferiority of using hydrogen as fuel in the gas turbine engine. Abstract: The main objective of this paper is to perform thermodynamic analysis of a TF33 turbofan engine fueled by hydrogen as opposed to kerosene. Considering the performance parameters, environmental indicators, and sustainability metrics of the TF33 operating with hydrogen and kerosene, a comprehensive thermodynamic comparison is achieved. In addition, its performance, and its environmental, and sustainability assessments are thermodynamically evaluated. Accordingly, the following is noticed at the take-off phase as an outcome of a transition from the kerosene-turbofan to the previously mentioned hydrogen-turbofan: ( i ) The fuel flow reduces by 63.83%; ( ii ) The specific fuel consumption decreases by 60.61%; ( iii ) The energy efficiency reduces by 0.757%; ( iv ) The thermal limit ratio decreases by 1.55%; ( v ) The fuel cost rate increases by 290.91%; ( vi ) The environmental effect factor (EEF) for combustion chamber (CC) increases by 14.25%; ( vii ) and the sustainable efficiency factor (SEF) and exergetic sustainability index (ESI) for CC reduce by 6.72% and 12.51%, respectively. In addition, the benefits and drawbacks of using hydrogen as fuel in the engine are presented comprehensively under the guidance of the results. The main contribution of this research lies in whether or not the result of using hydrogen as a fuel in gas turbine engines by employing thermodynamic analysis results in a more efficient and more environmentally friendly engine.